The prediction of transfer pricing manipulation among public listed companies in Malaysia / Adzhamsyah Abdul Hamid, Roshayani Arshad and Nur Farahah Mohd Pauzi. - Abdul Hamid, Adzhamsyah; Arshad, Roshayani; Mohd Pauzi, Nur Farahah (Universiti Teknologi MARA Cawangan Selangor, 2015)
Transfer pricing has become one of the main issues in the Malaysian tax perspectives since the pioneer legal case has proven to attract more scrutiny and supervision of the related authorities. In 2012, the comprehensive act by the Inland Revenue board to replace the Transfer Pricing Guidelines 2007is believed to curb any manipulation and malpractice among related party transactions. This study aims to examine the relationships between three risk indicators of transfer pricing and the probability of transfer mispricing practices among Public Listed Companies (PLCs) in Malaysia. Using a micro backward-looking approach for seventy companies consisting of 350 firm-years provides evidence that the number of tax haven subsidiaries and gross profit margin affected the extent of Effective Tax Rate yielded. These findings show that transfer pricing practices among PLCs may amount to a serious tax evasion scheme if the practices are not properly controlled and monitored by the authorities.